Novel automated method to assess group dynamics reveals deficits in behavioral contagion in rats with social deficits - Smirnov, Kirill; Starkov, Ilya; Sysoeva, Olga; Midzyanovskaya, Inna (Frontiers in Behavioral Neuroscience, 2024)
Behavioral copying is a key process in group actions, but it is challenging for individuals with autism spectrum disorder (ASD). We investigated behavioral contagion, or instinctual replication of behaviors, in Krushinky-Molodkina (KM) rats (n = 16), a new potential rodent model for ASD, compared to control Wistar rats (n = 15). A randomly chosen healthy Wistar male (“demonstrator rat”) was introduced to the homecage of experimental rats (“observers”) 10–14 days before the experiments to become a member of the group. For the implementation of the behavioral contagion experiment, we used the IntelliCage system, where rats can live in a group of 5–6 rats and their water visits can be automatically scored. During the experiment, the demonstrator was taken out of IntelliCage for a pre-test water deprivation and then placed back for the behavioral contagion test. As a result, a drinking behavior of the water-deprived demonstrator rat prompted water-seeking and drinking behaviors in the whole group. Unlike the Wistar controls, KM observers showed fewer visits to the drinking bottles, particularly lacking inspection visits (i.e., visits without drinking). The control group, in contrast, exhibited a dynamic, cascade-like visiting of the water corners. The proportion of activated observers in KM rats was significantly lower, as compared to Wistar ones, and they did not mimic other observer rats. KM rats, therefore, displayed an attenuated pattern of behavioral contagion, highlighting social deficits in this strain. This study suggests that measuring group dynamics of behavioral contagion in an automated, non-invasive setup offers valuable insights into social behavior in rodents.